A família sapotaceae na planície litorânea de Picinguaba-Ubatuha/SP - Carneiro, Cláudia Elena [UNESP]; De Assis, Marco Antonio [UNESP] (My University, 1996)
A taxonomic study is provided for the angiosperm family Sapotaceae based on specimens collected on the coastal plains of Picinguaba, municipality of Ubatuba, State of São Paulo, Brazil. The samples were gathered monthly from 1988 to 1991 and are kept in the Herbarium Rioclarense (HRCB). Six species and five genera are here presented with descriptions, !lustrations and identification key.
The family sapotaceae on the coastal plains of Picinguaba-Ubatuba, state of São Paulo, Brazil
Keywords: Coastal plains; Picinguaba; Sapotaceae